Identificação parasitológica, sorológica e molecular de Dirofilaria immitis na região metropolitana do Rio de Janeiro - Chocobar, Marianna Laura Elis [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Dirofilariosis, a zoonotic disease caused by the parasites Dirofilaria immitis and Dirofilaria repens, is transmitted by mosquitoes and affects dogs, cats, and occasionally humans. Known as “heartworm disease,” this infection can lead to signs of right-sided heart failure in dogs, respiratory syndrome in cats, and often results in death in both species. In Brazil, knowledge about dirofilariosis is limited, particularly regarding its prevalence in cats, the distribution of D. repens, and its presence in non-coastal areas. This Thesis aims to: i) identify the prevalence of dirofilariosis in dogs and cats in urban and suburban regions of Rio de Janeiro; ii) identify risk factors associated with infection; iii) apply robust diagnostic methods in animals from low-income owners, facilitating diagnosis and treatment; and iv) evaluate the inflammatory response in positive animals through haptoglobin measurement. The prevalence of canine dirofilariasis was significantly higher in suburban areas (14.47%) compared to urban areas (6.17%) (p = 0.003), while none of the tested cats yielded positive results. Dogs older than two years showed a higher risk of infection (p < 0.001), while characteristics such as breed, sex, size, coat type, use of macrocyclic lactones, or access to outdoor environments were not identified as predictive factors. This study reinforces the evidence that the prevalence of D. immitis is increasing in areas previously considered non-endemic and suggests that environmental and socioeconomic factors may play an important role in determining the current epidemiological status of this parasite. The research conducted here regionalizes and internationalizes science, and the results provide a basis for control and awareness measures, reinforcing the need for ongoing studies to improve understanding and control of this emerging and neglected disease in Brazil.

A dirofilariose, uma doença zoonótica causada pelos parasitos Dirofilaria immitis e Dirofilaria repens, é transmitida por mosquitos e afeta cães, gatos e, ocasionalmente, humanos. Conhecida como a “doença do verme do coração,” essa infecção pode provocar sinais de insuficiência cardíaca direita em cães, síndrome respiratória em felinos, e frequentemente leva ao óbito em ambas as espécies. No Brasil, há conhecimento limitado sobre a dirofilariose, especialmente em relação à prevalência em gatos, à distribuição de D. repens e à presença da doença em áreas não litorâneas. Esta Tese propõe: i) identificar a prevalência de dirofilariose em cães e gatos nas regiões urbana e suburbana do Rio de Janeiro; ii) identificar fatores de risco para a infecção; iii) aplicar métodos de diagnóstico robustos em animais de tutores de baixa renda, facilitando o diagnóstico e tratamento; e iv) avaliar a resposta inflamatória em animais positivos por meio da dosagem de haptoglobina. A prevalência para Dirofilariose canina foi significativamente maior nas áreas suburbanas (14,47%) com respecto al área urbana (6,17%) (p = 0,003), enquanto nenhum dos gatos testados teve resultados positivos. Cães com mais de dois anos apresentaram maior risco de infecção (p < 0,001), enquanto características como raça, sexo, porte, tipo de pelagem, uso de lactonas macrocíclicas ou acesso a ambientes externos não se mostraram fatores preditivos. Este estudo reforça as evidências de que a prevalência de D. immitis está aumentando em áreas anteriormente consideradas não endêmicas e sugere que fatores ambientais e socioeconômicos podem desempenhar papel importante na determinação do atual status epidemiológico desse parasito. As pesquisas aqui desenvolvidas fornecem base para medidas de controle e conscientização, reforçando a necessidade de estudos contínuos para aprimorar a compreensão e o combate dessa doença negligenciada no Brasil.
Identificación parasitológica, serológica y molecular de Dirofilaria immitis en la región metropolitana de Rio de Janeiro
Parasitological, serological and molecular identification of Dirofilaria immitis in the metropolitan region of Rio de Janeiro
Keywords: Diagnóstico; Dirofilariose; Epidemiologia; Saúde Única; Vetores